‘Talkin’ ‘Bout My Generation’: Using a Mixed-Methods Approach to Explore Changes in Adolescent Well-Being across Several European Countries - Cosma, Alina; Belić, Jelisaveta; Blecha, Ondřej; Fenski, Friederike; Lo, Man Y.; Murár, Filip; Petrovic, Darija; Stella, Maria T. (Frontiers in Psychology, 2017)
The promotion of positive mental health is a becoming priority worldwide. Despite all the efforts invested in preventive and curative work, it is estimated that one in four persons will experience a mental health condition at some point in their lives. Even more worrying is the fact that up to a half of all mental health problems have their onset before the age of 14. Recent statistics (national & international surveys, meta-analyses, international reports) point out to the fact that child and adolescent mental health problems are on the rise. The present study will try to corroborate these results and further explore their meaning, by employing a sequential mixed methods research design (quantitative-qualitative). The quantitative part will analyse time trends using Health Behaviours in School-aged Children (HBSC) data (four survey cycles: 2002, 2006, 2010, 2014) on mental well-being from four European countries (the Czech Republic, Germany, Italy, and the United Kingdom). The qualitative part will rely on focus groups to explore the perspectives of 13- and 15-year-old boys and girls on gender differences and on the changes in adolescent mental well-being over time, as well as measures through which these issues could be addressed. Thematic analysis will be employed to analyse qualitative data. The results of this study could make a major contribution to our understanding of the current trends in adolescent mental well-being, as well as the ways in which existing data could be linked to international and national health policies.